DNMT1 downregulation as well as its overexpression distinctly affect mostly overlapping genes implicated in schizophrenia, autism spectrum, epilepsy, and bipolar disorders - Singh, Minali; Saxena, Sonal; Mohan, Kommu Naga (Frontiers in Molecular Neuroscience, 2023)
Data on schizophrenia (SZ), epilepsy (EPD) and bipolar disorders (BPD) suggested an association of DNMT1 overexpression whereas certain variants of the gene were predicted to result in its increased expression in autism spectrum disorders. In addition, loss of DNMT1 in frontal cortex resulted in behavioral abnormalities in mice. Here we investigated the effects of increased as well as lack of DNMT1 expression using Dnmt1tet/tet neurons as a model for abnormal neurogenesis and 10,861 genes showing transcript level dysregulation in datasets from the four disorders. In case of overexpression, 3211 (~ 30%) genes were dysregulated, affecting pathways involved in neurogenesis, semaphorin signaling, ephrin receptor activity, etc. A disproportionately higher proportion of dysregulated genes were associated with epilepsy. When transcriptome data of Dnmt1tet/tet neurons treated with doxycycline that downregulated DNMT1 was used, 3356 genes (~31%) were dysregulated with a significant proportion involved in pathways similar to those in untreated cells. Both conditions resulted in ~68% of dysregulated genes wherein a majority showed similar patterns of transcript level changes. Among the genes with transcripts returning to normal levels, ribosome assembly/biogenesis was most significant whereas in absence of DNMT1, a new set of 903 genes became dysregulated and are involved in similar pathways as mentioned above. These findings provide support for overexpression of DNMT1 as well as its downregulation as risk factors for the four disorders and that its levels within a tight range is essential for normal neurodevelopment/mental health.